2018
DOI: 10.1093/ntr/nty088
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Factors Influencing Smoking Following Release From Smoke-Free Prisons

Abstract: Interventions designed to help people remain abstinent from tobacco following release from smoke-free prisons are an important opportunity to improve the health, finances and well-being of this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…Moreover, resumption after release from a smoke-free prison appears to be very high in the few studies reporting on this topic. 41 70 72–75 For instance, according to one systematic review, 76 >60% of former smokers relapsed on the first day after release, and almost all resumed smoking within 6 months of release. Despite this high rate of relapse another systematic review, 77 based on many of the same studies, commented that the rate of relapse varied too much to draw any clear conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, resumption after release from a smoke-free prison appears to be very high in the few studies reporting on this topic. 41 70 72–75 For instance, according to one systematic review, 76 >60% of former smokers relapsed on the first day after release, and almost all resumed smoking within 6 months of release. Despite this high rate of relapse another systematic review, 77 based on many of the same studies, commented that the rate of relapse varied too much to draw any clear conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Forced abstinence in a growing number of jails and prisons that have adopted tobacco-free policies 41 confers health benefits for some people while in custody 10 , 42 but such bans are inconsistently enforced, meaning that many continue to smoke while incarcerated, 41 and have otherwise been shown to accomplish little in preventing high rates of smoking relapse following release from custody. 18 , 22 Such findings further support the need for integrated treatment approaches to smoking cessation for those managing co-occurring mental illness and/or SUD following return to the community, 39 particularly because criminal justice involvement may represent rare or even first-time access to smoking cessation for many who are incarcerated 43 and evidence has shown that appropriate interventions in incarcerated settings are effective. For example, one study found that a behavioral intervention combining elements of motivational interviewing with cognitive-behavioral therapy significantly improves the likelihood of continued cessation post-release 44 and another showed more moderate success with an intervention combining pharmacotherapy with brief in-custody counseling.…”
Section: Discussionmentioning
confidence: 76%
“…These may include high rates of mental illness, drug abuse, and problem alcohol use, each of which suggest a need for integrated treatment approaches to smoking cessation that account for mental health and SUD treatment needs, for example, combining pharmacotherapy and engagement in regular cognitive-behavioral therapy over a sustained period of time (eg, 7-10 weeks). [37][38][39] The use of integrated treatment approaches in addition to intensive tobacco dependence interventions in this population is further supported by the fact that nearly half of smokers in this study said they had used cessation resources like counseling and the nicotine patch or gum unsuccessfully in the past.…”
Section: Discussionmentioning
confidence: 82%
“…However, the findings suggest non-compliance with smokefree rules and relapse to smoking following liberation may potentially constrain longer-term health benefits ( de Andrade and Kinner, 2016 ). For this reason, several commenters have advocated for smokefree prison policy to be accompanied by evidence-based cessation interventions which seek to strengthen smokers’ readiness to change and support individuals to sustain abstinence in prison and beyond ( Butler et al , 2007 ; Puljevic and Segan, 2018 ; Ritter, 2014 ).…”
Section: Introductionmentioning
confidence: 99%